APPLICATION OF PLANT BIOMASS COMPOST APPLICATION AND THE USE OF SEVERAL TYPES OF mulch ON THE GROWTH AND PRODUCTION OF RED ONION (allium ascalonicum L.) - Muhammad Randi Satria; Erni Hawayanti; Neni Marlina; Nico Syahputra Sebayang (Universitas Islam Negeri Ar-Raniry, 2022)
Shallots are agricultural commodities that are always ordered, especially as a cooking spice. Without shallots, it feels as if there is something incomplete in the taste of the dish. To increase the production of shallots it is necessary to modify the cultivation. This study aims to determine the type of mulch and the dose of organic fertilizer from plant waste that has the best effect on the growth and production of shallot (Allium ascalonicum L). The research was carried out from April to July 2021 on the farmer's land, Jalan Sukarela Lr. Batujajar RT.18 KM 7 Sukarame Subdistrict, Palembang. This study used the Experimental Method with a Divided Plot Design consisting of 12 treatment combinations which were repeated 3 times to obtain 36 plots. Factor I = Mulch Type (M) consisting of 3 levels: M1 = Black Silver Plastic Organic Mulch, M2 = Water Hyacinth Organic Mulch, M3 = Jengkol Bark Organic Mulch. Factor II = Plant-waste Organic Fertilizer Dosage (L) consisting of 4 levels: L0 = Chemical Fertilizer According to Recommended Dosage, L1 = 5 tons/ha (1kg/plot), L2 = 10 tons/ha (2kg/plot) L3 = 15tons /ha (3kg/plot). The variables observed were plant height (cm), number of tubers per clump (tubers), tuber weight per plot (grams). The combination treatment of jengkol skin organic mulch with a dose of organic fertilizer from plant waste of 15 tons/ha (3kg/plot) gave the highest effect on the growth and production of shallots at 850.00 grams/plot or equivalent to 8.50 tons/ha.